2020
DOI: 10.3904/kjim.2018.158
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward advance directives and prognosis in patients with heart failure: a pilot study

Abstract: Background/Aims: Advance directives (ADs) in Korean patients with heart failure (HF) and the associations of attitude towards ADs and HF prognosis with ADs were initially assessed using the model of the Korean-Advance Directive (K-AD). Methods: Twenty-four patients with HF (age, 67.1 years; men, 58.3%; ejection fraction, 35.9%) participated. A pilot test to evaluate the feasibility of ADs and the possible associations of attitudes towards ADs and prognosis with end-of-life treatment preferences among patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
6
0
4
Order By: Relevance
“…Previous studies reported similar EoL values for cancer patients, but subtle differences were noted in comfortable dying (73.8%), which was primarily valued the most, and pain relief, which was primarily desired the most (47.4%), followed by no burden on family (21.1%) and both (5.3%) [22]. Community-dwelling chronically ill elders [22] and patients with heart failure [30] also highly valued comfortable dying (35.0% and 48.4%, respectively), followed by no burden on family (28.6% and 19.4%, respectively). Furthermore, approximately half of the respondents preferred aggressive treatments such as CPR, ventilator support, and hemodialysis.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies reported similar EoL values for cancer patients, but subtle differences were noted in comfortable dying (73.8%), which was primarily valued the most, and pain relief, which was primarily desired the most (47.4%), followed by no burden on family (21.1%) and both (5.3%) [22]. Community-dwelling chronically ill elders [22] and patients with heart failure [30] also highly valued comfortable dying (35.0% and 48.4%, respectively), followed by no burden on family (28.6% and 19.4%, respectively). Furthermore, approximately half of the respondents preferred aggressive treatments such as CPR, ventilator support, and hemodialysis.…”
Section: Discussionmentioning
confidence: 84%
“…The non-awareness of ADs in the majority of patients with HF may be one reason for this lack of a significant relationship given the lack of variability in knowledge. In a pilot study, patients with HF reported knowledge deficit as a major reason for incomplete K-AD survey [ 41 ]. Thus, further research is warranted to examine this relationship in larger sample studies with more variability in knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the associational relationships of the diagnostic contexts with EoL treatment preferences, we also examined possible associations of AD attitudes and perceived susceptibility with EoL treatment preferences because prior studies showed possible associations of AD attitudes and perceptions with an individual's decisions for the desired EoL treatments [26][27][28][29]43]. However, little is known about these links.…”
Section: Plos Onementioning
confidence: 99%
“…Based on several prior studies that reported substantial burdens of care [10,11,13] and demands for future EoL care planning [12,13], but less access to ACP in patients with HF [12,24] compared to the cancer population [12], this study hypothesized that diagnostic contexts (non-cancer HF vs. cancer) would be associated with consideration of an AD with primary decision-making for LST options, such as cardiopulmonary resuscitation (CPR) [10,24]. In addition, such a decision may be influenced by some modifying factors, such as attitudes toward ADs [26,27] and perceived susceptibility to AD use [28,29]. We also hypothesize that a person with more positive attitudes and greater perceived importance for having unexpected EoL experiences without an AD is more likely to consider an AD.…”
Section: Introductionmentioning
confidence: 99%